The Related Factors to the Behaviour of Pregnant Women in Maternity Planning and Complication Prevention Program - Elsa Surya; Dewi Rahayu; Aila Karyus (Indonesian Journal of Global Health Research, 2021)
One of the breakthrough efforts that can reduce the maternal mortality rate as is Maternity Planning and Complication Prevention is expected to motivate the behavior of pregnant women in an effort to accelerate the reduction of maternal mortality. The high maternal mortality rate in Pringsewu regency is caused by a lack of screening for pregnant woman because it is suspected that there are still many high – risk pregnant woman who have not been found or have not come to health facilities. The aim of the research is knowledge of factors associated with behavior of pregnant women in childbirth planning and complication prevention programs. This research is a quantitative study with a cross sectional design. The data was collected by questionnaire tool. The population in this study were pregnant women who had an antenatal care in January 2021 at 3 public health centers that representing Pringsewu Regency, namely the community health center which had the highest moderate, and lowest coverage of Pregnancy visits 1 and 4 visits as many as 122 pregnant women. While the sample in this study was 96 pregnant women. Before the data collection, a questionnaire was tested on 30 respondents. The data analysis in this study is univariate test, bivariate test, and multivariate test. Based on the results of the study, it is known that some of pregnant women in Pringsewu regency have good behaviour, namely 62,5%. The results showed that there were 5 variables that had a significant relationship with the behavior of pragnant women in complication preventif program including knowledge (p value 0,030),attitudes (p value 0,000), availability of infrastructure (p value 0,033), distance to health facilities (p value 0,030) and husband’s support (p value 0,017). The most dominant variable related to the behaviour of pregnant women in complication prevention program is attitude where has the highest OR value of 5,881. In order to inprove the behavior of the community,especially pregnant women in complication prevention program, the Departement of Health needs to empower the community such as implementing the standby village, so that the community is able to independently fulfill the health facilities or infrastructure that are not yet available, namely village ambulances and village blood banks to support the implementation of complication prevention program so as to reduce maternal mortality rate (MMR) and infant mortality rate (IMR).